Ferromagnetic Coupling in an Fe[C(SiMe3)3]2/Ferrihydrite Hetero‐Mixture Molecular Magnet. Issue 20 (4th June 2014) - Kuzmann, Ernő; Zoppellaro, Giorgio; Pechousek, Jiri; Cuda, Jan; Klencsár, Zoltán; Homonnay, Zoltán; Tucek, Jiri; Szalay, Roland; Pápai, Mátyás; Machala, Libor; Zboril, Radek
Abstract: Magnetization and low temperature in‐field 57 Fe Mössbauer spectroscopy measurements have been performed on a Fe[C(SiMe3 )3 ]2 /ferrihydrite hetero‐mixture. The results indicate the presence of ferromagnetic coupling of magnetic moments involving Fe[C(SiMe3 )3 ]2 with a hyperfine magnetic field of about 151 T, attributable mainly to the non‐frozen atomic orbital contribution. The present findings show the sensitivity of single‐ion molecular magnets to local alterations of their lattice‐environment and might explain and reconcile some of the differences found in the literature for the observed bulk magnetic properties of the title Fe[C(SiMe3 )3 ]2 compound. Abstract : The presented Mössbauer spectroscopy and magnetic susceptibility study performed on a Fe[C(SiMe3 )3 ]2 /ferrihydrite hetero‐mixture showed that the single ion molecular magnet, Fe[C(SiMe3 )3 ]2, displayed an effective magnetic field of 156 T at 5 K in an external magnetic field of 5 T, indicating ferromagnetic coupling in the Fe[C(SiMe3 )3 ]2 /ferrihydrite magnetic material.